Epidemiological Study of Unintentional Poisonings of Patients Referred to Teaching Hospitals in Shahroud in 2020-2022 - Salamatmanesh, Maryam; NaseriBooriAbadi, Tahereh; Daliri, Salman; Amiri Largani, Hossein (Shahroud Journal of Medical Sciences, 2026)
Background: Poisonings are a significant cause of hospital admissions and can lead to serious health issues, including death. Since the causes of poisoning can vary by region, it is essential to identify them for effective diagnosis and treatment. This study examined the patterns of unintentional poisonings among patients at Shahroud teaching hospitals. Methods: This study employed a descriptive cross-sectional design to collect data on patients hospitalised for unintentional poisoning at hospitals affiliated with Shahroud University of Medical Sciences. Data collection occurred from March 20, 2020, to March 20, 2022, using a researcher-developed checklist. The data were analysed using both descriptive and analytical statistical tests in SPSS version 22. Results: A total of 377 individuals were hospitalised for unintentional poisoning, with a mean age of 29.57 years. Among the cases studied, 65% were male, while 55.4% were single, and 69.5% lived in urban areas. Notably, 92.8% reported no prior history of alcohol consumption, 65.5% had no addiction issues, and 89.7% had no mental disorders. Most poisonings occurred in spring (27.1%), particularly in April (10.6%), at night (47.7%), and in the home (58.1%). Oral ingestion was the primary method (89.1%), with medications being the leading cause (53.3%). Methadone was the most hazardous substance, contributing to 18.8% of poisoning incidents. Patients typically arrived at the hospital within 30 to 60 minutes (62.3%) and stayed for 2 to 4 days (55.4%). Antidotes were needed for 41.4% of patients, with naloxone prescribed in 35.5% of cases. Following their recovery, 67.4% were discharged. Non-medicinal poisoning was most prevalent in children under five years of age and individuals over 46 years of age (P-value<0.001), while medicinal poisoning was more common in urban areas (P-value=0.003). Conclusions: Studying the patterns of unintentional poisonings in a specific region can greatly enhance prevention and management strategies, ultimately saving lives. The results of this research enable healthcare providers to make informed clinical decisions and contribute to the development of practical guidelines for managing poisoning. By enhancing health and quality of life for individuals, this research undoubtedly reduces the financial burden on the healthcare system.